Pengaruh Sumber Daya Manusia, Teknologi Informasi dan Komitmen Organisasi Terhadap Tingkat Penerapan Standar Akuntansi Pemerintah Berbasis Akrual (Studi Kasus Pada Organisasi Perangkat Daerah (OPD) Pemerintah Kota Gorontalo) - Avania Putri Zalni; Rio Monoarfa; Nurharyati Panigoro (Economics and Digital Business Review, 2022)
The objectives of this research were to determine 1) the effect of human resources, information technology, and organizational commitment partially on the level of implementation of accrual-based government accounting standards in the Regional Apparatus Organization of Gorontalo City Government; 2) the effect of human resources, information technology, and organizational commitment simultaneously on the level of the implementation of accrual-based government accounting standards in the Regional Apparatus Organization of Gorontalo City Government. In addition, the research employed quantitative research where the data analysis technique used was multiple regression analysis. The research finding revealed that; partially, human resources positively and significantly affected the level of implementation of accrual-based government accounting standards in the Regional Apparatus Organization of Gorontalo City Government; and information technology positively and significantly affected the level of implementation of accrual-based government accounting standards in the Regional Apparatus Organization of Gorontalo City Government. On the other hand, partially, organizational commitment negatively and insignificantly affected the level of implementation of accrual-based government accounting standards in the Regional Apparatus Organization of Gorontalo City Government. Simultaneously, human resources, information technology, and organizational commitment affected the level of implementation of accrual-based government accounting standards in the Regional Apparatus Organization of Gorontalo City Government.